Phytotherapeutic potential of herbal extracts on male reproductive organs in rat models - A.A. Ammari; A.R. Alhimaidi; R.A. Amran; A. Rady; H. aljawdah (Arquivo Brasileiro de Medicina Veterinária e Zootecnia, 2025)
ABSTRACT This study investigates the phytotherapeutic potential of herbal extracts on male reproductive organs using rat models. Herbal extracts, recognized for their bioactive properties such as antioxidation and hormone modulation, were evaluated for their effects on testicular function, spermatogenesis, and reproductive hormone levels. A polyherbal formulation consisting of Ziziphus spina-christi, Trigonella foenum-graecum, and Nigella sativa (ZTN) was prepared and administered to male rats at two doses (100mg and 250mg) for 14 days. Biochemical analysis revealed a dose-dependent impact on testosterone, luteinizing hormone (LH), and follicle-stimulating hormone (FSH) levels. Histological examination demonstrated mild to severe disruptions in spermatogenesis and testicular architecture, particularly at the higher dose. While the 100mg dose exhibited mild positive effects on sperm quality and testicular weight, the 250mg dose resulted in testicular degeneration and reduced spermatozoa, indicating potential toxicity. The findings suggest that while herbal extracts hold promise for male reproductive health, appropriate dosing is crucial to avoid adverse outcomes.